(3JHjf GdMbGFb aj nCnLd GdNdbs - (3Gdabjgj GdYjfj, eMeOs ((3CMeO Hf EHQGgje GdchR dMUGQjs)
(3ChdgG (B:s
(3GdMeO ddg GdcHjQ GdeJYGd GdefRg Yf GdTQjc hGdeKGd hHYO ajbhd GdabjQ eMeO Gdabgj GdYjfj fRd bSWfWjfI bO GYJbO cKjQ ef GdeMOKjf hGdeTGjN GdUhajI Gf GdCYeGd GdUGdMI cGdUObI hGdUdI JRjO aj GdYeQ hCf GdaSb hGdXde jfbUg hMcehG HCf ddNdGFb CLdjf eYdb heHQe CdaJ gPg GdQSGdI hSejJgG JHjf GdMb aj CLd GdNdbs
(3BNQgG (B:s
(3hgh eefhY TQYG EP aj JWhjdg cSd Yf GdWGYI hGdJShja ddJhHI hGdQZHI aj GdOfjG hGdfSjGf ddBNQI hGdbShI ddbdH ceG fUhG Ydjg hCeG OYGA GdfLGJ (B( (3cPG (B) (3ef GdYPGH agh YHGOI hbO GeQ GdfHj Udi Gddg Ydjg hSde HPdc Ohf GdChd ceG eQ ajeG QhGg GHf eSYhO ef MOjK MHjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds